Customizing subcutaneous immunoglobulin administration in primary antibody deficiency: patient-centric care perspectives - Kobayashi, Roger H; Maltese, Joanna; Litzman, Jiří; Kreuwel, Huub; Zekoll, Theresa; Kobayashi, Ai Lan; Gupta, Sudhir (Immunotherapy, 2024)
This report delves into the challenges and potential solutions associated with flexible, customized subcutaneous immunoglobulin (SCIG) infusion regimens for patients with primary antibody deficiency disease (PAD). Advances in the treatment of inborn errors of immunity, particularly PAD, have converted fatal diseases into chronic, complex, long-term conditions that make adherence to treatment a critical issue. Conventional SCIG infusion regimens, while clinically effective, may not always align with the varied lifestyles, changing lifestyles and commitments of patients which can lead to missed doses, diminishing adherence thus posing potential health risks and compromising the overall effectiveness of treatment. For these reasons, it's important to develop flexible infusion regimens tailored to meet individual patient needs. Patient-centric strategies that promote shared decision-making and awareness of patient status not only promote medical efficacy but also enhance the overall patient experience. The authors of this report call attention for a need to shift toward more adaptable and individualized SCIG treatment plans for PAD patients whose needs may change over the long-term course of treatment.
Keywords: Primary Immunodeficiency Diseases; Cutaquig; pasivní imunizace; Immunization, Passive; primary antibody deficiency disease; péče orientovaná na pacienta; lidé; Precision Medicine; Humans; injekce subkutánní; primární imunodeficience; patient-centric; Infusions, Subcutaneous; Immunoglobulin replacement therapy; individualizovaná medicína; shared decision-making; Patient-Centered Care; subcutaneous immunoglobulin; Injections, Subcutaneous; subkutánní infuze